Literature Review Factors Causing Low Interested Implants Contraception - Sitti sarti; Fabiola Francisca Martins Soares; Marilia De J. Dos Reis; Niken Wahyu Hidayati (Fakultas Ilmu Kesehatan, 2023)
To cope with the growth of the human population, the government makes policies to anticipate the population explosion which is increasing every year. One of them is the family planning (KB) program, this program aims to control births for married couples. This program has existed and been implemented in Indonesia since 1957 until now. From government programs, in fact there are contraceptive methods in Indonesia that are low in demand, one of which is the implant method. The implant method in Indonesia does tend to be small when compared to other long-term methods. The BKKBN stated that implant users in 2019 were only 7.4%, far below the pill and injection methods. In his study, (Putri, Rahma, 2015) concluded that knowledge has a relationship with the choice of implant contraceptive types. There are several factors that influence the low use of implant contraception in Indonesia. Studies conducted by (Triyanto, L. Indriani, 2018) stated that age, education, employment and family planning service sources could influence the use of Long-Term Contraceptive Methods (MKJP) in Women of Reproductive Age (WUS) including in the selection of implants as a contraceptive method. This literature review uses a narrative research study of the literature which describes the factors causing the low interest in contraceptive implants. The sample uses 5 research articles. The conclusion from this literature review is that age, knowledge, perceptions of the mother and sources of information are the factors causing the low interest in KB implant acceptors. In addition, there is the participation of health workers, cadres and all levels of society to support the implementation of counseling and good KIE so that information about family planning implants reaches the community properly and correctly. It is hoped that family planning service providers will provide even better efforts in sharing information and counseling and KIE about family planning implants to acceptors and prospective family planning acceptors. Researchers hope that the results of this study can be used as a reference for further research with a wider range of variable